MEMAKNAI HUKUM ACARA TATA USAHA MILITER DALAM PENYELESAIAN SENGKETA TATA USAHA MILITER SEBAGAI BENTUK IMPLEMENTASI ASAS EQUALITY BEFORE THE LAW. (Lex Jurnalica, 2022)
In a legal state, the existence of the trias politica consists of : laws of power, executive power, and judicial power, laws of the power to make laws, executive power whose implementation of the function of action or application, and lastly, the power of the judiciary is the judge whose implementation or function of adjudication of rules. Trias politica is the function of this power to prevent the abuse of power by those in power. It is hoped that the human rights of citizens will not be degraded. The doctrine of separation of powers, as for in the concept of law there are three powers, statutory power, executive power, and judicial power, the third power must be separate for the duties and functions of the judicial institutions in particular there is the independence of the individual, human rights are waged and at stake. This study uses normative laws, based on empirical. Normative legal research on the effectiveness of the rule of law issues, as well as resolving military administrative disputes in accordance with the rule of law, legal implications, the impact of the application of dispute resolution norms later. Formulation of the problem: a. How should the settlement of military administrative disputes be carried out in accordance with the rule of law?, b. What are the juridical implications for the inconsistency of the legal norms governing the settlement of military administration disputes?